2014
DOI: 10.1177/0890334414548860
|View full text |Cite
|
Sign up to set email alerts
|

A Clinic-Based Breastfeeding Peer Counselor Intervention in an Urban, Low-Income Population

Abstract: Breastfeeding rates in all women improved during the study period. Breastfeeding attitude was more strongly associated with breastfeeding behavior than peer support. Peer counseling supported women with low self-efficacy and helped women achieve their breastfeeding goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 23 publications
(38 reference statements)
2
61
0
2
Order By: Relevance
“…29,34,35,[37][38][39][80][81][82][83][84][85][86][87][88][89] Nine interventions were delivered in the USA, all associated with the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC). [80][81][82][83][84][85][86][87]89 Five papers related to UK-based interventions 34,35,[37][38][39]88 and one intervention was delivered in Canada. 29 Studies were included if they pertained to a model of BFPS that included planned one-to-one contact between a mother and a peer supporter, reported breastfeeding rates (initiation, continuation or exclusivity) as an outcome measure and if they had been delivered in a developed country setting.…”
Section: Rapid Evidence Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…29,34,35,[37][38][39][80][81][82][83][84][85][86][87][88][89] Nine interventions were delivered in the USA, all associated with the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC). [80][81][82][83][84][85][86][87]89 Five papers related to UK-based interventions 34,35,[37][38][39]88 and one intervention was delivered in Canada. 29 Studies were included if they pertained to a model of BFPS that included planned one-to-one contact between a mother and a peer supporter, reported breastfeeding rates (initiation, continuation or exclusivity) as an outcome measure and if they had been delivered in a developed country setting.…”
Section: Rapid Evidence Reviewmentioning
confidence: 99%
“…Eleven studies were RCTs, 29,34,35,37,80,81,84,[86][87][88][89] three were area-based controlled studies 38,82,83 and two were natural experiments. 39,85 Applying Cochrane risk of bias criteria, 91 we found that only three studies had a low risk of bias.…”
Section: Study Qualitymentioning
confidence: 99%
See 3 more Smart Citations